2011
DOI: 10.2174/092986711795843191
|View full text |Cite
|
Sign up to set email alerts
|

Branched Peptides for the Modulation of Protein-Protein Interactions: More Arms are Better than One?

Abstract: Combinatorial peptide libraries from synthetic or biological sources have been largely used in the last two-decades with the aim of identifying bioactive peptides that specifically bind proteins and modulate their interactions with other protein partners. Differently from biological libraries, synthetic methods allow the development of different kinds of libraries based on two main characteristics: i) the use of building blocks and chemical bonds different from those naturally occurring and ii) the possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Similarly, peptidomimetics, cyclic peptides and stapled peptides are being increasingly used to inhibit PPIs (Refs 35, 36). These ligands mimic natural protein–protein contacts by presenting multiple amino acid side chains from architecturally complex cores (Refs 37, 38, 39, 40, 41). Finally, small-molecule–protein hybrids have been developed to artificially increase apparent molecular mass and target the most difficult PPIs (Refs 42, 43).…”
Section: Challenges Of Targeting Ppismentioning
confidence: 99%
“…Similarly, peptidomimetics, cyclic peptides and stapled peptides are being increasingly used to inhibit PPIs (Refs 35, 36). These ligands mimic natural protein–protein contacts by presenting multiple amino acid side chains from architecturally complex cores (Refs 37, 38, 39, 40, 41). Finally, small-molecule–protein hybrids have been developed to artificially increase apparent molecular mass and target the most difficult PPIs (Refs 42, 43).…”
Section: Challenges Of Targeting Ppismentioning
confidence: 99%
“…Specifically, multimeric peptides are reported to be critical for increasing recognition of cell surfaces while promoting tissue stability (Grove et al 2008). Likewise, multimerization of a bioactive monomeric peptide enhances interaction between target surfaces and peptides; however, multimeric peptides do not create new recognition sites (e.g., RGD will always bind to SH3 domains; Ruvo et al 2011). Thus, our results could be a consequence of an enhanced interaction of the trimeric RGD and α 5 β 1 , α 8 β 1 , α V β 1 , α IIb β 3 , α V β 3 , α V β 5 , and α V β 6 integrin receptors (Ruoslahti 1996) with an enhanced contact of the trimeric YIGSR and α 3 β 1 , α 4 β 1 , and α 6 β 1 integrin receptors (Maeda et al 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The linear, cyclic, multimeric, and branched structures have been used as scaffolds into which natural or non-natural amino acids have been inserted to increase the chemical diversity or to achieve a more rigid conformation and more stable structures (17). Several reports have demonstrated that increasing the copy number of a precursor peptide by multimerization is a simple and effective way to enhance immunogenicity, affinity, and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multimeric peptides have been described in the literature as an obvious solution to increase peptide size and affinity while maintaining the original amino acid sequence (17)(18)(19), and this approach is a key strategy to increase recognition surfaces and/or stability. Increasing the peptide size also increases the difficulty of identifying peptides with high affinity and selectivity; however, multimeric peptides comprising simple branched structures and a short arm may offer an optimal compromise between molecular size and the ease of preparation, yield, and purity of the final product.…”
mentioning
confidence: 99%